Research methods - Theresa L White (Australia Wadsworth Cengage Learning, 2013)
Provides psychology students with a scientific approach to understanding their field of study and the world in general. This title illustrates the many creative ways that psychology professionals design and conduct effective research
Psychology and Science -- Developing a Research Question -- Ethics in Research -- Writing in Psychology -- Variables -- Validity -- Control -- Nonexperimental Research, Part I: Observational, Archival and Case-Study Research -- Nonexperimental Research, Part 2: Survey Research -- True Experiments, Part 1: Single-Factor Designs -- True Experiments, Part 2: Factorial Designs -- Single-Subject Experiments -- Quasi Experiments -- Data Exploration PartI: Graphic and Descriptive Techniques -- Data Exploration, Part 2: Inferential Statistics.
Keywords: Psychology, Experimental - Methodology. Psychology -Research - Methodology